Implementation of the Crossword Puzzle Method in Improving the Results of Understanding the Material on the Prophet's Story in the Aqidah Akhlak Lesson at MIS As Syarifiyah - Budiyanti, Yeni; Lidya, Yayah; Heryanti, Yeti; Nuryani, Yani (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to analyze the effectiveness of the application of the Crossword Puzzle method in improving students' understanding of the material on the story of the prophet in the lesson of Akidah Akhlak in class 4 MIS As Syarifiyah in the 2024/2025 academic year. The Crossword Puzzle method was chosen because it can provide a more enjoyable learning experience, increase student involvement, and help strengthen their memory of the material being studied. This study uses a classroom action research (CAR) method consisting of several cycles, including the planning, implementation, observation, and reflection stages. The subjects of the study were 11 students of class 4 MIS As Syarifiyah. Data collection was carried out through observation, interviews, and material understanding tests before and after the application of this method. The results of the study showed a significant increase in students' understanding of the material on the story of the prophet after the application of the Crossword Puzzle method. This is evidenced by the increase in the comprehension test scores from each cycle carried out. In addition, students become more active, motivated, and enthusiastic in the learning process. Thus, the Crossword Puzzle method can be used as an innovative and effective learning strategy in improving students' understanding of the material on Akidah Akhlak.